Особливостi видiлення етилену мiжвузлями кукурудзи (Zea mays L.) - Щербатюк, М.М.; Маменко, Т.П. (Видавничий дім "Академперіодика" НАН України, 2008)
The intensity of ethylene emission in growing maize stem internodes is studied. The most intensive ethylene biosynthesis in maize internodes is ascertained for the early stages of development (5 leaves), and the least intensive one - for older stages (a ﬂowering of panicle). So, during the maize development, the high and low levels of ethylene accumulation are typical of, respectively, rapidly growing top internodes and lower internodes.